Forest logging is associated with shape of males and gynes in the wood ant Formica aquilonia - Sorvari Jouni; Haatanen Marja K. (SPRINGER BASEL AG, 2022)
Environmental stress can affect individual development and fitness in insects. Forest logging is a serious environmental stress for forest-specialist insects, such as the mound-building wood ant Formica aquilonia Yarrow 1955, which builds its nests into forests and is dependent on the nutrition provided by the forest habitat. We studied whether the logging causes such a strong environmental stress that it would be visible in disproportionate growth and shape of young winged wood ant gynes ('queens') and males. We measured head width, thorax width and wing length of 144 gynes and 100 males from 12 nests from six clear-cut areas, 11 nests from unlogged forest stands and 10 nests in clear-cut-forest margins. We observed disproportionate growth of different body parts and allometric growth of wings in both sexes in areas with different logging-induced disturbance. Gynes had larger heads in clear-cut areas and males had narrowest thoraxes in forest clear-cut edges. With an increasing thorax width, the wing length decreases steeper in clear-cuts than in other habitats in gynes and increases steeper in clear-cuts than other habitats in males. It seems that in a strongly disturbed clear-cut environment, the gynes invest the growth of head width. There seems to be a trade-off between the growth of the thorax and wings in gynes but not in males. The altered body shape may be adaptation to clearings caused by storm events of wild fires, but not forest management practices of modern era. Large-headed gynes may be better in a colony take-over, needed for the establishment of new colonies in early succession stage habitats in this temporally social parasitic species. Long-winged males may have better long-range flight ability, and they may thus have better fitness and change to disperse their genes onto new habitats.